Odpowiedzi

Najlepsza Odpowiedź!
2009-09-29T14:18:05+02:00
A) 3x/5 - 2x-4/5 = (3x - 2x + 4)/5 = x+4 / 5
b) a/3x + 3/5x = (5ax + 9x)/15x² = (5a + 9) / 15x
c) x/a-5 - x+2/5-a = x/a-5 + x+2/a-5 = 2x+2 / a-5
1 4 1
2009-09-29T14:18:47+02:00
Wykonaj dodawanie i odejmowanie:
a) 3x/5 - 2x-4/5= 3x- 2x+4 /5=x+4 /5
b) a/3x + 3/5x=5a /15x+9/15x=5a+9 /15x
c) x/a-5 - x+2/5-a=x/a-5 + x+2/a-5=x+ x+2/a-5= 2x+2/a-5
1 5 1
2009-09-29T14:44:33+02:00
A) 3x/5 - 2x-4/5= 3x- 2x+4 /5=x+4 /5
b) a/3x + 3/5x=5a /15x+9/15x=5a+9 /15x
c) x/a-5 - x+2/5-a=x/a-5 + x+2/a-5=x+ x+2/a-5= 2x+2/a-5